2022
DOI: 10.2147/jir.s342462
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Specific Lung Microbiota with Metabolic Profiles in Bronchoalveolar Lavage Fluid Between Infectious and Inflammatory Respiratory Diseases

Abstract: Background: Infiltration of the lower respiratory tract (LRT) microenvironment could be significantly associated with respiratory diseases. However, alterations in the LRT microbiome and metabolome in infectious and inflammatory respiratory diseases and their correlation with inflammation still need to be explored. Methods: Bronchoalveolar lavage samples from 44 community-acquired pneumonia (CAP) patients, 29 connective tissue disease-associated interstitial disease (CTD-ILD) patients, and 30 healthy volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In Fig. 1, we found the main bacterial phyla in the United States [32][33][34], Asia [35][36][37][38][39] and Europe [40][41][42][43] remain completely consistent. In the normal tissues of patients [44][45][46][47][48][49], four main bacterial phyla (Proteobacteria, Firmicutes, Actinobacteria and Bacteroidetes) were shared with healthy subjects.…”
Section: Five Phyla Dominating In All Studies About Healthy Subjectsmentioning
confidence: 67%
“…In Fig. 1, we found the main bacterial phyla in the United States [32][33][34], Asia [35][36][37][38][39] and Europe [40][41][42][43] remain completely consistent. In the normal tissues of patients [44][45][46][47][48][49], four main bacterial phyla (Proteobacteria, Firmicutes, Actinobacteria and Bacteroidetes) were shared with healthy subjects.…”
Section: Five Phyla Dominating In All Studies About Healthy Subjectsmentioning
confidence: 67%
“…Prevotella is known to promote the production of inflammatory cytokines, but the genus contains many different species, some of which may play different roles than other members. Yukun He reported that the abundance of Prevotella was decreased in both CAP and CTD-ILD patients and was negatively correlated with white blood cell counts and CRP levels ( 1 ). Unfortunately, we did not get that result.…”
Section: Discussionmentioning
confidence: 99%
“…Connective tissue disease-associated interstitial lung disease (CTD-ILD) and community-acquired pneumonia (CAP) are heterogeneous lung diseases ( 1 ). They are all characterized by inflammatory lesions in the lungs.…”
Section: Introductionmentioning
confidence: 99%
“…For patients diagnosed with pneumonia, bronchoscopy was performed as a part of clinical management within 72 h after hospital admission before the ventilation treatments. Detailed sampling procedures, pretreatment, and storage were performed as described in previous studies ( Zheng et al., 2019 ; He et al., 2022 ). Sampling controls were collected through simulated bronchoscopy procedures (no patient) using the same instrument and method.…”
Section: Methodsmentioning
confidence: 99%